Study of reading habits 1981 - Sundsvall - Weibull, Lennart (University of Gothenburg, 1993)
This survey forms part of the research program ´Dagspresskollegiet´, a program considering the local population´s reading habits and attitudes toward the local press. Inhabitants of Sundsvall were asked about how often they read a number of specified papers and if they were subscribers; if they had subscribed earlier and reason for interruption; changes of morning paper the last ten years; subscription for morning paper the last ten years, choice of newspaper and reason for this choice; changes of paper, and reason why; purchase of single copies for a number of papers; regulary reading of local morning paper; time spent with the morning paper; amount read of different contents; availability of local morning paper at place of work; opinions on different front pages; the importance of coulored pictures in the morning paper; the importance of advertisement when choosing a newspaper; important contents of a morning paper. The respondents also had to indicate if they agreed or disagreed with a number of statements on newspapers, radio and television. Other questions dealt with how often the respondent watched or listened to a number of news programs in radio and television and opinion on most reliable news source. Furthermore the respondents had to mention events 1980-1981 that was especially remembered - in the municipality, in Sweden and abroad respectively; interest in politics and local events; party preferred and line preferred at the referendum on nuclear power; organizational membership and activities. A battery of questions dealt with the local paper Sundsvalls Tidning specifically. Finally the respondents were asked about their background and had to indicate important changes of their life during the seventies.

This survey forms part of the research program ´Dagspresskollegiet´, a program considering the local population´s reading habits and attitudes toward the local press. Inhabitants of Sundsvall were asked about how often they read a number of specified papers and if they were subscribers; if they had subscribed earlier and reason for interruption; changes of morning paper the last ten years; subscription for morning paper the last ten years, choice of newspaper and reason for this choice; changes of paper, and reason why; purchase of single copies for a number of papers; regulary reading of local morning paper; time spent with the morning paper; amount read of different contents; availability of local morning paper at place of work; opinions on different front pages; the importance of coulored pictures in the morning paper; the importance of advertisement when choosing a newspaper; important contents of a morning paper. The respondents also had to indicate if they agreed or disagreed with a number of statements on newspapers, radio and television. Other questions dealt with how often the respondent watched or listened to a number of news programs in radio and television and opinion on most reliable news source. Furthermore the respondents had to mention events 1980-1981 that was especially remembered - in the municipality, in Sweden and abroad respectively; interest in politics and local events; party preferred and line preferred at the referendum on nuclear power; organizational membership and activities. A battery of questions dealt with the local paper Sundsvalls Tidning specifically. Finally the respondents were asked about their background and had to indicate important changes of their life during the seventies.
Läsvanestudien 1981 - Sundsvall
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap